2016
DOI: 10.3746/pnf.2016.21.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aqueous Extracts of Cynanchum wilfordii in Rat Models for Postmenopausal Hot Flush

Abstract: Menopausal hot flushes (HFs), which manifest as a transient increase in skin temperature, occur most frequently in postmenopausal women, and sometimes negatively influence daily life. We investigated the effect of an aqueous extract of Cynanchum wilfordii (CWW) in a rat model of menopausal HFs, where tail skin temperature (TST) is increased after the rapid estrogen decline induced by ovariectomy. Ten-week-old female rats were ovariectomized and treated with CWW for 1 week. We measured TST and rectal temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Our previous study reported that C. wilfordii inhibited the elevation of skin temperature in OVX rats and did not affect plasma estrogen activity and uterine weight [35]. In this study, CPAE (Cynanchum wilfordii Hemsley, Phlomis umbrosa Turcz., and Angelica gigas Nakai extract) effectively relieved hot flash, a symptom of menopause, in OVX rat models.…”
Section: Discussionmentioning
confidence: 59%
“…Our previous study reported that C. wilfordii inhibited the elevation of skin temperature in OVX rats and did not affect plasma estrogen activity and uterine weight [35]. In this study, CPAE (Cynanchum wilfordii Hemsley, Phlomis umbrosa Turcz., and Angelica gigas Nakai extract) effectively relieved hot flash, a symptom of menopause, in OVX rat models.…”
Section: Discussionmentioning
confidence: 59%
“…For example, caudatin, 2,4-dihydroxyacetophenone, 2,5-dihydroxyacetophenone, 4-hydroxyacetophenone, and baishouwubenzophenone were all isolated from CA , CB and CW , indicating there were close relationships among them [ 24 , 25 , 26 , 27 , 28 , 29 ]. C 21 -steroids (deacylmetaplexigenin, rostratamine, wilfoside C1G, cynanauriculoside E, kidjoranin, cyanoauriculoside A, wilfoside M1N), acetophenones (cynandione A–B, cynandione E), and other compounds (leucanthemitol, suceinie acid, sucrose, methyleugenol) were all obtained from CA and CW , which might strengthen the relationship between them [ 5 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Bungeiside C, bungeiside D and 2- O -β-laminaribiosyl-4-hydroxyacetophenone were obtained from CB and CW , thereby revealing their close relationship between them [ 42 , 43 ].…”
Section: Botanymentioning
confidence: 99%
“…Ten-week-old female rats were ovariectomized (OVX) and treated with the aqueous extract of CWW for 1 week. The administration of CWW (200 mg/kg/d for 7 days, per os) significantly improves skin temperature increase in OVX rats [ 119 ]. Moreover, the aqueous extract of CWW inhibits the development of benign prostatic hyperplasia (BPH) in a testosterone-induced BPH rat model [ 120 ].…”
Section: Pharmacologymentioning
confidence: 99%